1996
DOI: 10.1111/j.1095-8649.1996.tb00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and taxonomic relationships among Far‐Eastern salmonid fishes inferred from mitochondrial DNA divergence

Abstract: Mitochondrial DNA (mtDNA) restriction analysis was used to examine the evolutionary and taxonomic relationships among 11 taxa of the subfamily Salmoninae. The genera Brachymystax and Hucho were closely related, diverging by sequence divergence estimates of 3·1%. Because the mtDNA sequence divergence between blunt-and sharp-snouted forms of Brachymystax (2·24%) was similar to divergence level of Brachymystax and Hucho, then taking into account the distinct morphological, ecological and allozyme differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…In all of our supermatrix analyses, Parahucho perryi was sister to the ( Salvelinus , Oncorhynchus ) group, corroborating other findings [4], [10], [21], [22], [31], [81]. Strong support for the genus validity of Parahucho and its sister taxa designation with ( Salvelinus , Oncorhynchus ) was obtained both in the maximum likelihood (99% bootstrap value) and Bayesian (100% posterior probability) analyses on MitoNuc-NT despite the conflicting genomic signals detected in the MP analysis on that supermatrix.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In all of our supermatrix analyses, Parahucho perryi was sister to the ( Salvelinus , Oncorhynchus ) group, corroborating other findings [4], [10], [21], [22], [31], [81]. Strong support for the genus validity of Parahucho and its sister taxa designation with ( Salvelinus , Oncorhynchus ) was obtained both in the maximum likelihood (99% bootstrap value) and Bayesian (100% posterior probability) analyses on MitoNuc-NT despite the conflicting genomic signals detected in the MP analysis on that supermatrix.…”
Section: Discussionsupporting
confidence: 90%
“…Divergence times throughout our phylogeny are generally older than those estimated by some previous studies [27], [31], [102][105]. It is important to interpret these estimates with caution.…”
Section: Discussionmentioning
confidence: 49%
“…Nonetheless, hybrids exist [[24-26], Additional File 1], some evidence of introgression has been reported [28] and in captivity, F 1 hybrids and their progeny (backcrosses and F2) are viable [Alekseev S., unpublished data]. Thus, one or more mechanisms must be operating to prevent higher levels of introgression, such as selection against hybrids in nature.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study based on the isozymes LDH, MDH, ADH, GDH and EST (Qin & Wang, 1989), showed overlap between B. tsinlingensis and B. lenok. However, mtDNA data are considered more efficient in delineating fish species (Meyer, 1993;Hillis et al 1996) and has been broadly used in taxonomic studies of Salmonidae (Shedko et al 1996;Hansen et al 2003;Xia et al 2006;Froufe et al 2008;Crete-Lafreniere et al 2012;Si et al 2012;Shedko et al 2013;Liu et al 2014).…”
Section: Ditscussionmentioning
confidence: 99%